Oral administration of bitter gourd (Momordica Charantia) extract prevent dyslipidemia on male wistar rats (rattus norvegicus) fed with high-fat diet - Hendrik Danico; Wimpie Pangkahila; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Dyslipidemia is one of the most prevalent health conditions and often leads to development of many chronic diseases such as coronary artery disease, heart failure, and stroke. This study was conducted to investigate the effects of bitter gourd (Momordica Charantia) extract on lipid profiles in male wistar rats fed with high-fat diet. Methods: This study was an experimental research using randomized post-test only control group design. The subjects were 36 male Wistar rats (Rattus norvegicus) randomly divided into 2 groups. The first group was the control group (P0) and fed with placebo while the treatment group (P1) received bitter gourd (Momordica Charantia) ethanol extract at 1g/kg body weight/day. Both groups were fed with high fat diet. The experiment was lasted for 35 days and lipid profiles were measured at the end of the experiment. Results: Statistical analysis results revealed the mean of total cholesterol, triglyceride, and low-density lipoprotein (LDL) in the treatment group were significantly lower than control group while high-density lipoprotein (HDL) was significantly higher in the treatment group (p<0.05). Conclusion: This study concluded that bitter gourd extract significantly prevent dyslipidemia on male Wistar rats fed with high-fat diet.